PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VII SMP NEGERI 002 PASARIBU HUMBANG HASUNDUTAN - Hesti Diah Pratiwi Simamora; Makhdalena; Filma Alia Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of learning motivation on student learning outcomes in the subject of Social Studies of class VII SMP Negeri 002 Pasaribu Humbang Hasundutan. Learning outcomes are one of the important indicators in the world of education that reflect how effective the learning process is carried out. This study uses a quantitative descriptive approach. The population in this study were 329 students of class VII SMP Negeri 002 Pasaribu. The sample size used the Slovin formula which resulted in 77 students. The sampling technique used proportional random sampling. The data collection technique used a questionnaire for the learning motivation variable and documentation of final semester exam scores for learning outcomes. The types of data in this study are primary data for the learning motivation variable sourced from students and secondary data for the learning outcome variable sourced from the school. Data were analyzed using simple linear regression. The results showed that learning motivation had a significant effect on the learning outcomes of students of SMP Negeri 002 Pasaribu Humbang Hasundutan Regency. The t-test showed that learning motivation had a significant effect on learning outcomes with a significance value of 0.015.